Universal Algebra I policy, access, and inequality: Findings from a national survey - Janine T. Remillard; John Y. Baker; Michael D. Steele; Nina D. Hoe; Anne Traynor (Arizona State University, 2017)
Many in the US view algebra as a gatekeeper to advanced study of mathematics, and increasing enrollment in algebra courses as a strategy to address unequal access to educational opportunity. As a result, universal enrollment policies, which require all students to complete Algebra I by grade 8 or 9, have garnered attention in school districts or states. Based on a view that school districts are the primary implementers of state and national policy in the US, this study surveyed a nationally representative sample of districts to investigate the prevalence of such policies and their relationship to algebra enrollment. Districts reported substantial increases in Algebra I enrollments in eighth grade, although ninth grade remains the most common year students enroll. Only 26% of districts reported having universal enrollment policies; in these districts, linear regression indicated that an association with higher eighth grade Algebra I enrollment was moderated by poverty level (measured by FRL). As a result, universal policies, while decreasing within-district disparities, may increase disparities between districts. These disparities may be explained by maximally maintained inequality (Raftery Hout, 1993) and effectively maintained inequality theories (Lucas, 2001), which posit that more affluent groups take deliberate action to perpetuate inequalities.